Analysis Of The Performance Of Sharia Microfinance Institutions In The Harapan Sejahtera Cooperative Is Measured By The Islamicity Performance Index Approach - Alleynisa, Amanda; Bakhri, Syaeful; Bushtomi, Achmad Otong (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
Islamicity Performance Index is one of the financial performance measurement methods used to assess the extent of the principles of justice, halalness and purification in a cooperative, therefore, the study aims to find out and analyze the financial performance of the Harapan Sejahtera Cooperative which is measured by several indicators from the Islamicity Performance Index approach. This study uses a quantitative approach with secondary data in the form of financial statements of the Harapan Sejahtera Cooperative in 2018-2022 and uses the Islamicity Performance Index measurement method. Based on the results of the study, the performance of the Harapan Sejahtera Cooperative in 2018-2022 has carried out the overall implementation of the Islamicity Performance Index, but it has not been maximized in its operations.